Simplifying words in context. Experiments with two lexical resources in Spanish. (January 2016) - Saggion, Horacio; Bott, Stefan; Rello, Luz
Abstract : Highlights: We developed the first lexical simplification for Spanish. Human-informed evaluation of the system. Comparison of two WSD strategies. Comparison of two lexical resources. Software and dataset made available for testing and verification. Abstract: In this paper we study the effect of different lexical resources for selecting synonyms and strategies for word sense disambiguation in a lexical simplification system for the Spanish language. The resources used for the experiments are the Spanish EuroWordNet, the Spanish Open Thesaurus and a combination of both. As for the synonym selection strategies, we have used both local and global contexts for word sense disambiguation. We present a novel evaluation framework in lexical simplification that takes into account the level of ambiguity of the word to be simplified. The evaluation compares various instances of the lexical simplification system, a gold standard, and a baseline. The paper presents an in-depth qualitative error analysis of the results.